PENGARUH PENDEKATAN REALISTIC MATHEMATIC EDUCATION TERHADAP KETERAMPILAN BERPIKIR KRITIS PADA PEMBELAJARAN GEOMETRI SISWA KELAS IV SDN PILANG I - Putri, Laily Santinia Rahmah; Murni, Arie Widya (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2023)
This research is motivated by low critical thinking skills which is caused by the lack of effectiveness of learning in the classroom. Approach used by the teacher in the classroom makes students passive and afraid because they think that mathematics is a difficult and scary subject, so this study aims to determine the effect of a realistic mathematics education (RME) approach on the critical thinking skills of grade IV students at Pilang 1 Elementary School with 20 students. The importance of teachers to implement fun and real learning can improve students' critical thinking skills. This research method is quantitative with a quasi-experimental research type and uses a one-group pretest and posttest research design. The results obtained in this study are thumg = 9.94 and > ttable = 2.09. The average pretest score was 49.70 while the posttest had an increase of 72.77. This shows that there are differences in pretest and posttest scores after the implementation of RME, so it can be concluded that the RME approach has an effect on students' critical thinking skills in learning mathematics.